Canadian Experience with the Pipeline Embolization Device for Repair of Unruptured Intracranial Aneurysms - O'Kelly, C.J. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Flow-diverting stents, such as the PED, have emerged as a novel means of treating complex intracranial aneurysms. This retrospective analysis of the initial Canadian experience provides insight into technical challenges, clinical and radiographic outcomes, and complication rates after the use of flow-diverting stents for unruptured aneurysms. MATERIALS AND METHODS: Cases were compiled from 7 Canadian centers between July 2008 and December 2010. Each center prospectively tracked their initial experience; these data were retrospectively updated and pooled for analysis. RESULTS: During the defined study period, 97 cases of unruptured aneurysm were treated with the PED, with successful stent deployment in 94 cases. The overall complete or near-complete occlusion rate was 83%, with a median follow-up at 1.25 years (range 0.25–2.5 years). Progressive occlusion was witnessed over time, with complete or near-complete occlusion in 65% of aneurysms followed through 6 months, and 90% of aneurysms followed through 1 year. Multivariate analysis found previous aneurysm treatment and female sex predictive of persistent aneurysm filling. Most patients were stable or improved (88%), with the most favorable outcomes observed in patients with cavernous carotid aneurysms. The overall mortality rate was 6%. Postprocedural aneurysm hemorrhage occurred in 3 patients (3%), while ipsilateral distal territory hemorrhage was observed in 4 patients (3.4%). CONCLUSIONS: Flow-diverting stents represent an important tool in the treatment of complex intracranial aneurysms. The relative efficacy and morbidity of this treatment must be considered in the context of available alternate interventions.